Design and analysis of dynamically grouped multilevel space-time trellis code - Jain, Dharmvir (My University, 2015)
The wireless communication systems are expected to support high speed multimedia services such as high speed internet access, mobile gaming, and high definition video transmission. The rapidly growing demand of these services is driving the communication technology towards reliable and high data rate transmission. In this research work, design and analysis of different dynamically grouped multilevel space-time trellis codes have been presented in order to support the rising demand for higher data rate and higher reliability in the wireless communication systems. The simulation results depict that the proposed codes provide better performance than existing multilevel space-time trellis codes (MLSTTCs) and grouped multilevel space-time trellis codes (GMLSTTCs). The proposed codes may be applied in the wireless communication systems such as GSM, CDMA, TDMA, and FDMA. MLSTTCs and GMLSTTCs consider channel state information (CSI) at the receiver only without considering the CSI at the transmitter. In this research work, effects of the CSI at the transmitter have been considered to improve the performance of MLSTTCs and GMLSTTCs. The CSI has been used to dynamically select a component space-time trellis code (STTC), adaptively group the transmit antennas, and provide a beamforming scheme for dynamic distribution of the transmit power across the transmit antennas. MLSTTCs and GMLSTTCs use predefined STTCs as the component codes in the multilevel coding. A code set selection algorithm has been proposed for dynamic selection of the generator sequences with the help of the CSI at the transmitter. The selected generator sequences are used to design dynamic space-time trellis codes (DSTTCs). The simulation results show that the coding gain of DSTTCs is superior to existing STTCs by 0.7 dB at frame error rate (FER) of 10-2. DSTTCs are used as the component code in multilevel coding for designing multilevel dynamic space-time trellis codes (MLDSTTCs) and grouped multilevel dynamic space-time trellis codes (GMLDSTTCs). It may be inferred from the results that MLDSTTCs are superior to MLSTTCs by 1.1 dB at FER of 10-1 and GMLDSTTCs are superior to GMLSTTCs by 1.6 dB at FER of 10-2. GMLSTTCs use static grouping of transmit antennas. In the presented research work, the performance of GMLSTTCs has been improved by performing the adaptive grouping of the transmit antennas based on the CSI. Adaptively grouped multilevel space-time trellis codes (AGMLSTTCs) have been designed by grouping the transmit antennas with the help of the CSI at the transmitter. An adaptive antenna grouping algorithm has been proposed to perform the transmit antenna grouping. Instantaneous channel power gain is calculated between each transmit antenna and all the receive antennas. A subset of transmit antennas having maximum instantaneous channel power gain is selected to form a group of transmit antennas. From the presented results, it is evident that AGMLSTTCs are superior to GMLSTTCs by 1.5 dB at the FER of 10-2. In GMLSTTCs, the transmit power is equally distributed across all transmit antennas. The performance of GMLSTTCs has been improved by dynamically allocating the power to the transmit antennas. Weighted adaptively grouped multilevel space-time trellis codes (WAGMLSTTCs) and weighted adaptively grouped multilevel dynamic space-time trellis codes (WAGMDLSTTCs) have been designed by weighting the transmitting signals based on the CSI at the transmitter. It has been shown that the performance of WAGMLSTTCs is better than GMLSTTCs by 2.6 dB and the performance of WAGMDLSTTCs is superior to GMLSTTCs by 3.2 dB.
Doctor of Philosophy, Electronics and Communication, Thesis
Keywords: STBC; STTC; MLSTTC; multilevel codes; space time trellis code; electronics; electronics and communication